Pravni vidiki uporabe umetne inteligence v delovnih razmerjih - Uredba (EU) 2024/1689 o določitvi harmoniziranih pravil o umetni inteligenci in slovenski zakon o izvajanju uredbe - Mašera, Damjan (Delavci in delodajalci, 2026)
The article analyses the use of artificial intelligence in recruitment and in the regulation of employment relationships. The AI Act classifies HR systems as high-risk, meaning that employers, as their deployers, must comply with a range of strict technical and organisational obligations. Slovenia has aligned its national legal framework with the requirements of the European regulation through the ZIUDHPUI and has designated the competent supervisory authorities and (strict) administrative offence sanctions.
Keywords: AI Act; Akt o UI; artificial intelligence; človeški nadzor; delovna razmerja; discrimination; diskriminacija; employment relationships; highrisk systems; human oversight; recruitment and workforce management; transparency; transparentnost; umetna inteligenca; visokotvegani sistemi; zaposlovanje in upravljanje delavcev; ZIUDHPUI